Inventory Control Analysis of Manual Hospital Bed Assembly Units PI-108MS, PI-208MS, PI-308MS with the EOQ (Economic Order Quantity) Method at PT. XYZ - Megawati, Ermayana; Fardiana, Arina; Saputra, Wahyu Sidiq; Hurun’in, Hurun’in; Ahmad, Tita Latifah (International Journal of Computer and Information System (IJCIS), 2022)
The purpose of this study is to determine the warehouse capacity of PT. XYZ in storing hospital bed supplies can use the EOQ( Economic Order Quantity)  method to determine the warehouse capacity in hospital bed supplies. The EOQ method seeks to achieve minimum inventory levels, lower costs and better quality. The EOQ method in the company will be able to minimize the occurrence of out of stock so that it does not interfere with the process and is able to save inventory costs incurred by the company. February showed that the company assembled 230 units, selling 151 units. Meanwhile, to avoid excess units, the number of assembly that must be done is 4,425 with the purchase of 2 units, Safety Stock 74.34 units and ROP 151 units. The calculation uses the EOQ method which shows that the safety stock that must always be available at PT. XYZ for unit inventory is as much as 230 units, meaning the company must have an inventory of 74.34 units in order to anticipate a shortage of units during the grace period without hampering the assembly process